Homenaje Aldo Medawar - Pasteris, Elizabeth; Gordillo, Susana; Olguín, Patricia; Puebla, Patricia Liliana; Farreras, Veronica (Cuyonomics. Investigaciones en Economía Regional, 2019)
Homenaje Aldo Medawar